There’s Nothing about Mary: The Insignificance of Mary in the Gospel of Thomas 114 - Anna Cwikla (Journal for Interdisciplinary Biblical Studies, 2019)
Feminist approaches to early Christian texts have consistently evaluated female characters as the primary focus of analysis. Yet in doing so, placing the spotlight on the female figure inevitably pushes male figures, and by extension, the broader context to the margins. This type of analysis runs the risk of overemphasizing the role of a woman in a given text while neglecting their narrative function in relation to male characters. This article looks specifically of Mary in the Gospel of Thomas. Previously, her role has seen her as one of the disciples in this text. But using Eve Sedgwick’s homosocial bond theory reveals that Gos. Thom. wishes to emphasize the relationship between Jesus and Peter more so than it does Mary. This example is but a case in point in seeing that although our focus as modern scholars shifts to the woman, the ancient text is more so concerned about the iteration of power structures between men over women.